Perancangan Perancangan Sistem Pengukuran Kapasitansi Crude Oil Menggunakan Interdigital Capasitors (IDCs) Berbasis Arduino Uno - Risse Entikaria Rachmanita; Haerul Ahmadi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
Arduino UNO R3 is one of the cheapest and easiest microcontroller boards that has great potential to be used as a basis for the measurement system. This study aims to develop measurement system of crude oil capacitance by using IDCs(Interdigital Capacitors). By knowing the value of crude oil capacitance, the crude oil permittivity value can be calculated. The crude oil permittivity value data is extremely needed in making crude oil heating systems using microwaves. The study used IDC sprinted on a PCB board with a copper layer as the electrode. Then, the system measurement results were compared with the results of PM 6303 RCL meter Phillip type A frequency measurement of 1 kHz which was used as reference data to determine the extent of measurement errors. From the results obtained, it is known that the error value of the Arduino UNO R3 based capacitance repeatability measurement is 0.47%. While the results of the linearity test measurement of crude oil capacitance measurement of temperature increases using the Arduino Uno-based IDCs sensor, the R2 value is 0.87. Thus it can be seen that the Arduino UNO R3-based capacitance measuring device has quite good sensor characteristics.